2004
DOI: 10.1080/14427591.2004.9686539
|View full text |Cite
|
Sign up to set email alerts
|

Offerings: Food Traditions of Older Thai Women at Songkran

Abstract: It is deep within our hearts that we have to do this." Such words reflect the potency of subjective and social meaning of food occupations for older Thai women at Songkran, the traditional Thai New Year. This paper presents the Thai findings from a multi-site research project exploring older women's experiences of food occupations at Songkran in Chiang Mai, Thailand; and Christmas in Auckland, New Zealand, and Kentucky, USA. Narrative data for this study were collected through focus group interviews with 33 Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…Within occupational science narrative data can range from addressing the lifespan of one individual (30,40) to brief incidents recounted by many individuals (67,68). For instance, life stories refer to information that can either cover an entire lifetime or pertain to specific aspects or periods within a lifetime (69)(70)(71)(72).…”
Section: Narrative Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Within occupational science narrative data can range from addressing the lifespan of one individual (30,40) to brief incidents recounted by many individuals (67,68). For instance, life stories refer to information that can either cover an entire lifetime or pertain to specific aspects or periods within a lifetime (69)(70)(71)(72).…”
Section: Narrative Datamentioning
confidence: 99%
“…In this analytic strategy, stories are commonly analyzed to extract themes, which provide insight into realms of meaning. In some instances, thematic analysis can be undertaken systematically in a way that allows multiple researchers to analyze the same data and consistently extract similar themes (43,67,73,80).…”
Section: Narrative Inquirymentioning
confidence: 99%
“…Participants in the study learned how to perform the occupation of saving turf from their parents and grandparents, and expressed a strong desire to share this leaning with their own (future) children in the same way. Wright-St Clair, Bunrayong, Vittayakorn, Rattakorn and Hocking, (2004) suggested that the transmission of particular ways of knowing and doing occupation between generations contributes to a generational consciousness, which in turn enhances collective ancestral identity. The sense of generational consciousness adds a further depth of meaning to performing an occupation, since in doing what has always been done participants are honouring the memory of their ancestors and ensuring continuity of an occupational heritage into the future.…”
Section: An Occupational Perspective Of Turf Cuttingmentioning
confidence: 98%
“…In one empirical study Schisler Connor & Polatajko (15) studied refugees and transformations in their everyday lives, while another study by Hocking et al (10,16) concerned cultural knowledge and everyday activities. In a refugee camp in Austria, Steindl et al (12) looked at how females handled the transformation in participation in everyday activities.…”
Section: Introductionmentioning
confidence: 99%